Indocyanine green fluorescence-guided surgery after IV injection in metastatic colorectal cancer: A systematic review. Issue 9 (September 2017) - Liberale, G.; Bourgeois, P.; Larsimont, D.; Moreau, M.; Donckier, V.; Ishizawa, T.
Abstract: Objective: Indocyanine green fluorescence-guided surgery (ICG-FGS) has emerged as a potential new imaging modality for improving the detection of hepatic, lymph node (LN), and peritoneal metastases in colorectal cancer (CRC) patients. The aim of this paper is to review the available literature in the clinical setting of ICG-FGS for tumoral detection in various fields of metastatic colorectal disease. Methods: PubMed and Medline literature databases were searched for original articles on the use of ICG in the setting of clinical studies on colorectal cancer. The search terms used were "near-infrared fluorescence", "intraoperative imaging", "indocyanine green", "human" and "colorectal cancer". Results: ICG fluorescence imaging (ICG-FI) is clearly supported as an intraoperative technique that allows the detection of additional superficial hepatic metastases of CRC. Data on the role of ICG-FI in the intraoperative detection of peritoneal metastases and LN metastases are scarce but encouraging and ICG-FI could potentially improve the staging and treatment of these patients. Conclusion: ICG-FI is a promising imaging technique in the detection of small infraclinic LN, hepatic, and peritoneal metastatic deposits that may allow better staging and more complete surgical resection with a potential prognostic benefit for patients.